2016
DOI: 10.1002/poc.3655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study on silver(I)-catalyzed aminofluorination of unactivated alkenes

Abstract: A study has been performed on the mechanism for the Ag(I)‐catalyzed intramolecular aminofluorination of N‐arylpent‐4‐enamides with Selectfluor by means of density functional theory. According to the calculations, the whole catalytic cycle consists of a series of elementary reactions, including formation of the complex (IMC) of the substrate and Ag(H2O)+ (derived from the ligation of H2O to Ag(I)), oxidation of the complex IMC by Selectfluor, deprotonation, homolytic cleavage of the N–Ag(II) bond, intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Interestingly, the key Ag(III)-F intermediate proposed by Li was observed to be less possible from the perspective of computa-tional chemistry. [19] Duan et al then reported a decarboxylative acylfluorination of styrene derivatives using α-oxocarboxylic acid as an acyl radical precursor in 2014 (Scheme 8a). [20] Later, the Li group reported a concise carbofluorination reaction of alkenes using acetic acid as radical source, affording a wide range of γ-fluorinated carboxylic acids with good functional group tolerance (Scheme 8b).…”
Section: Difunctionalization With the Fluorine Reagentmentioning
confidence: 99%
“…Interestingly, the key Ag(III)-F intermediate proposed by Li was observed to be less possible from the perspective of computa-tional chemistry. [19] Duan et al then reported a decarboxylative acylfluorination of styrene derivatives using α-oxocarboxylic acid as an acyl radical precursor in 2014 (Scheme 8a). [20] Later, the Li group reported a concise carbofluorination reaction of alkenes using acetic acid as radical source, affording a wide range of γ-fluorinated carboxylic acids with good functional group tolerance (Scheme 8b).…”
Section: Difunctionalization With the Fluorine Reagentmentioning
confidence: 99%